(untitled) (Journal of Parents and Teachers, 2015)
How to educate for a world that we can not even imagine? This is the great challenge we face nowadays. We live in the so-called Age of Intelligence, a moment of deep transformation that raises the need of innovation in our classrooms. How to go from a school that only teaches knowledge to a school that should train and teach thinking?. Nowadays there are pedagogical proposals that adapt well to research models as the one proposed by Howard Gardner, known as Theory of Multiple Intelligences. The application of this model in education has resulted well-established and recognized and have also extended to our own country. For Howard Gardner we are all intelligent; our goal as parents and teachers is to discover and develop the skills to learn. This new model of school education is not so much as the transmission of knowledge; but on the acquisition of skills that help develop thinking of our students and their ability to continue learning.